모델예측기반의 직접전력제어를 사용하는 AC/DC 및 DC/DC 컨버터의 동적응답특성 개선 - 최대근 (The Graduate School, Ajou University, 2015)
This paper proposes techniques for performance improvement and analyzes problems generated when model predictive direct power control (MPDPC) is applied to AC/DC/DC converter. Firstly, this paper presents a control scheme for the dynamic performance improvement of an AC/DC converter using the model predictive direct power control with duty cycle. In the MPDPC, the active and reactive powers are simultaneously controlled with a single cost function. If either of the two control targets has a large power variation, the control weight is concentrated on one side which causes the mutual interference. Because of such mutual interference, the control dynamics of the AC/DC converter deteriorates. Due to the control weight being concentrated on one side using the single cost function, the dynamic performance of the system is improved by reconfiguring the cost function that has the weighting factor to minimize the decline of the system dynamics which is caused by the mutual interference, even if the control dynamics of the other side decreases. The effectiveness of the proposed control scheme is verified by comparing its results with those of the conventional MPDPC. Secondly, it presents a model predictive direct power control for interleaved multiphase DC/DC converters. The power values necessary to adjust the output voltage in the succeeding are predicted using a converter model. The output power is controlled by selecting the optimal duty cycle. The proposed method does not require controller loopsand modulators for converter switching. This method can control the converter by calculating the optimal duty cycle, which minimizes the error between the reference and actual output voltage. The effectiveness of the proposed method is verified through simulations and experiments.
학위논문(박사)--아주대학교 일반대학원 :전자공학과,2015. 2
Keywords: 모델예측기반; 직접전력제어